STUDI REFRIJERAN RETROFIT DENGAN TIPE R-407C UNTUK MENGGANTIKAN R-22 DI UNIT REFRIJERAN PACKAGE PADA PROSES PRODUKSI GAS NITROGEN PT PTX - Abdurrohim, Muchlish
STUDY OF REFRIGERANT RETROFIT WITH R-407C TO REPLACE R-22 IN REFRIGERANT PACKAGE UNIT OF NITROGEN PRODUCTION PLANT PT PTX By Muchlish Abdurrohim NIM: 23016021 (Master’s Program in Chemical Enginering) The need for refrigerant replacement in the Refrigerant Package Unit in the process of producing nitrogen gas at PT PTX becomes large because the availability of R-22 refrigerant sources will be stopped due to environmental issues. Replacement of the R-22 refrigerant is carried out retrofitly without replacing the Refractory Package unit. Then it is necessary to study the possibility of using a new refrigerant namely R-407c. So as to ensure that there are no significant changes in operating conditions so that the Nitrogen Gas production unit remains in accordance with its capacity. Increased efficiency can be done by recommending the reuse of energy discharged by exchanging energy using a heat exchanger.